Physicochemical Characteristics, Fatty Acids Profile and Lipid Oxidation during Ripening of Graviera Cheese Produced with Raw and Pasteurized Milk - Maria D. Ioannidou; Martha Maggira; Georgios Samouris (Foods, 2022)
The production of cheese can be made from either pasteurized or non-pasteurized milk, depending on the country or dietary habits. In this work, the effect of pasteurization of milk on the progress of the physicochemical properties, fatty acids profile and lipid oxidation of cheese throughout a maturation period of 90 days is presented. This research was carried out on two types of Graviera cheese produced in Greece, one made from raw milk and the other from pasteurized milk. The proximal composition of each sample was evaluated, the fatty acids profile was analyzed by Gas Chromatography, whereas lipid oxidation was determined on the basis of the formation of malondialdehyde (MDA). Significant differences (p < 0.05) in the values of pH, fat and density between raw and pasteurized milk were observed. The physicochemical parameters during the ripening of the cheeses showed significant differences according to the type and the stage of maturation. Specifically, the two types of cheese differed significantly (p < 0.05) in terms of pH, protein, fat in dry matter (FDM), and water-soluble nitrogen/total nitrogen (WSN/TN). Although the fatty acids profile was similar for the two types of cheese, differences were observed during the ripening stages as well as between the milk and the final product. The lipid oxidation levels increased during maturation, whereas they seemed to be lower in the pasteurized cheeses. Therefore, it can be concluded that the use of raw or pasteurized milk affects the physicochemical characteristics, fatty acids profile and lipid oxidation of Graviera cheese during ripening.